Improving Tne Physical Fitness Of Students Through The Conduct Of Individual Programs - et. al., Mirzaev A.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, college students spare little time to the physical training, sport in universities. One of the factors of the current situation is an aberration in the development of physiological and psychological development of students. The article describes the main problems of implementation of physical activity of students in the framework of training in higher educational institutions. Problems of physical training of students can be divided into two groups of factors that influence the willingness of young people to physical activity. This objective (external) and subjective (internal), which in turn can be divided into physical and psychological. As a workaround, the active involvement of students in the process of physical self-education can be taken this form as organization of educational process as the development of individual programs of physical self-improvement, aimed at enhancing the creative work of self-education and physical self-improvement.